Controversies on Endocrine and Reproductive Effects of Glyphosate and Glyphosate-Based Herbicides: A Mini-Review - de Araújo-Ramos, Anderson Tadeu; Passoni, Marcella Tapias; Romano, Marco Aurélio; Romano, Renata Marino; Martino-Andrade, Anderson Joel (Frontiers in Endocrinology, 2021)
Glyphosate-based herbicides (GBHs) are among the most used pesticides worldwide, presenting high potential for human exposure. Recently, a debate was raised on glyphosate risks to human health due to conflicting views over its potential carcinogenic and endocrine disruptive properties. Results from regulatory guideline studies, reports from Regulatory Agencies, and some literature studies point to a lack of endocrine disrupting properties of the active ingredient glyphosate. On the other hand, many in vivo and in vitro studies, using different experimental model systems, have demonstrated that GBHs can disrupt certain hormonal signaling pathways with impacts on the hypothalamic-pituitary-gonadal axis and other organ systems. Importantly, several studies showed that technical-grade glyphosate is less toxic than formulated GBHs, indicating that the mixture of the active ingredient and formulants can have cumulative effects on endocrine and reproductive endpoints, which requires special attention from Regulatory Agencies. In this mini-review, we discuss the controversies related to endocrine-disrupting properties of technical-grade glyphosate and GBHs emphasizing the reproductive system and its implications for human health.